Lymphatic Filariasis in Children in Haiti. Issue 4 (July 2015) - Byrne, Sharon K.; Collins, Shonta D.
Abstract : Abstract: Using available evidence and astute assessment skills, nurses and advanced practice nurses, as members of an inter-professional team, were able to assess, diagnose, and initiate treatment for a child with lymphatic filariasis within a global health practice setting. The lessons learned during health outreach trips to an underserved commune of Port-au-Prince, Haiti can promote an understanding of appropriate nursing practice related to this parasitic infection. They can also assist nursing students, nurse practitioner students, and faculties as members of a medical outreach team to promote sustainability which is a benchmark of nursing leadership in global health. Abstract : Lymphatic Filariasis is a tropical disease common in Haiti. A pediatric case report is presented and includes a review of the disease, treatment plan, and follow-up care.